Finance and Development, June 1982. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1982)
This paper reviews the World Bank's graduation policy. Graduation of borrowers from the World Bank is a firmly established principle and has been a long-standing practice. Graduation is a logical step in the development process, and a clear set of guidelines for graduation from Bank lending is required. Graduation should be a flexible and fair process, sensitive to each country's individual circumstances. The paper highlights that the graduation policy was reaffirmed at a meeting of the Bank's Board of Executive Directors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet